A Reviuw: Sustainable Livestock Development in Indonesia - Munadi, Laode Muh; Hafid, Harapin; Aku, Achmad Selamet; Abadi, Musram (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2021)
The population of Indonesia in 2021 is about 273 million people. The increasing population is followed by an increase in food needs, including animal food. The area of land as a base of food production does not increase, even tends to decrease due to conversion, abrasion, and submerged seawater as a result of global warming and climate change, as well as the declining quality of natural resources. Animal protein consumption in Indonesia is very low and is expected to increase sharply as the income of the population continues to increase. Anticipating this, it is necessary to prepare a medium- and long-term farm development strategy in a sustainable manner by utilizing the availability of local resources. Exploring the genetic resources of livestock that are efficient in the use of feed, should also be able to utilize feed materials in the form of crop byproducts and agricultural industries. This policy should be supported by technological innovation and sustainable productivity and livestock production. Can save natural resources while reducing greenhouse gas emissions in order to realize the concept of green economy.